Fluorine adsorbent as well as preparation method and application thereof
The fluorine adsorbent with Sn(OH)4-xClx/PVC-PVB structure combined with PVC and PVB binder and MgCl2 regeneration liquid treatment solves the problems of low adsorption capacity and low regeneration efficiency of existing fluorine adsorbents. It realizes efficient and harmless treatment and the production of high-value-added products.
Patent Information
- Application Number
- CN202411586528.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-11-07
AI Technical Summary
The existing fluorine adsorbents have problems such as low adsorption capacity, unstable adsorption performance, low regeneration efficiency, and the inability to efficiently and harmlessly treat high concentrations of fluorine ions in the regeneration liquid.
The fluorine adsorbent with Sn(OH)4-xClx/PVC-PVB structure was prepared by precipitation reaction, oxidation reaction, drying and pulverization, powder granulation and fluorochloro-substitution steps. PVC and PVB are used as binders to form The adsorption channel is well connected to improve adsorption capacity and stability, and is efficiently regenerated and harmlessly treated through MgCl2 solution.
It has achieved high adsorption capacity, stable performance, high regeneration efficiency and high-concentration fluorine ions in the regeneration liquid, forming high value-added MgF2 powder, solving the shortcomings of existing fluorine adsorbents.
Smart Images

Figure CN119258973A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of adsorbents, and in particular to a fluorine adsorbent and a preparation method and application thereof. Background Art
[0002] Excessive fluoride in wastewater will not only cause serious environmental pollution, but also have a profound impact on human health. Therefore, it is necessary to take effective prevention and control measures and treatment technologies. At present, the treatment of low-concentration fluoride-excessive wastewater mainly adopts adsorption method. The core material of adsorption method is adsorbent. The performance of adsorbent directly affects the treatment effect of fluoride-containing wastewater.
[0003] For example: CN113842871A discloses an anti-interference defluorination adsorbent and its preparation method, which can resist the interference of bicarbonate in water, but the adsorption capacity of the defluorination material is low, only about 10 mg / g. CN112547021A discloses a biomass-based hydroxyapatite composite material and its preparation method and application, which can reduce the concentration of fluoride ions in a certain amount of fluorine-contaminated water to below 1.5 mg / L. However, the defluorination material of the invention, after adsorbing fluoride ions, uses a 5wt% sodium hydroxide + 5wt% sodium chloride alkali salt mixed solution to elute for 12h, the elution time is too long, and the regeneration efficiency is extremely low. CN112755972A discloses the preparation of a silicon-based resin and its application as a defluorination adsorbent. When the silicon-based resin of the invention is used as a defluorination adsorbent, it has high adsorption selectivity for fluoride ions, large adsorption capacity, and can be recycled. However, a large amount of toxic and harmful organic raw materials or solvents are used in the synthesis process of the fluorine adsorbent of the invention, which is easy to cause harm to the human body or the environment. CN112520811A discloses a manganese-loaded activated alumina defluorination adsorbent and a preparation method thereof. The manganese-loaded activated alumina defluorination adsorbent and a preparation method thereof provide enhanced adsorption capacity for fluoride ions, making the treated water more suitable for drinking. However, the defluorination material of the invention cannot be regenerated and recycled. CN114082407A discloses a preparation method for a defluorination adsorption resin, the fluoride ion concentration of the defluorination water produced by the defluorination resin cannot be less than 1 mg / L, and the high concentration of fluoride ions in the regenerated liquid has not been harmlessly treated.
[0004] As can be seen from the above, the existing commercially available fluorine adsorbents have the following disadvantages: low adsorption capacity, unstable adsorption performance, low regeneration efficiency, and the high concentration of fluoride ions in the regeneration liquid cannot be efficiently and harmlessly treated.
[0005] Therefore, it is necessary and urgent to research and develop a fluorine adsorbent with the advantages of large adsorption capacity, stable adsorption performance, high regeneration efficiency, and efficient and harmless treatment of high concentrations of fluoride ions in the regeneration liquid, so as to alleviate the technical problems of low adsorption capacity and unstable adsorption performance of existing fluorine adsorbents.
[0006] In view of this, the present invention is proposed. Summary of the invention
[0007] The first object of the present invention is to provide a fluorine adsorbent having the advantages of large adsorption capacity, stable adsorption performance, high regeneration efficiency, and efficient and harmless treatment of high-concentration fluorine ions in the regeneration liquid.
[0008] The second object of the present invention is to provide a method for preparing the above-mentioned fluorine adsorbent.
[0009] The third object of the present invention is to provide an application of the above-mentioned fluorine adsorbent in the treatment of fluorine-containing wastewater.
[0010] The fourth object of the present invention is to provide a method for treating fluorine-containing wastewater based on the above-mentioned fluorine adsorbent.
[0011] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0012] The present invention provides a fluorine adsorbent, the structural formula of which is: Sn(OH) 4-x Cl x / PVC-PVB, where: 0.8≤x≤1.0;
[0013] The PVC-PVB is a dual binder, and the fluorine adsorbent is prepared by using PVC and PVB as binders.
[0014] Furthermore, the fluorine adsorbent is a spherical structure, and the particle size of the fluorine adsorbent is 0.5 to 2 mm.
[0015] The present invention provides a method for preparing a fluorine adsorbent, the preparation method comprising:
[0016] S1 precipitation reaction: NaF-Na2CO3 solution is added dropwise to SnCl2-citric acid solution to perform precipitation reaction to obtain Sn(OH) 2-x F x Slurry;
[0017] S2 oxidation reaction: Sn(OH) 2-x F x The slurry is oxidized to make Sn(OH) 2-x F x Transformed to Sn(OH) 4-x F x , Sn(OH) 4-x F x Slurry;
[0018] S3 dry powder: Sn(OH) 4-x Fx The slurry was filtered to obtain Sn(OH) 4-x F x The filter cake is then dried and crushed to obtain Sn(OH) with a particle size of 0.5 to 20 μm. 4-x F x Powder;
[0019] S4 powder granulation: Sn(OH) 4-x F x Powder, PVC and PVB are added to the solvent to obtain a granulation solution; then drop ball granulation is performed to obtain Sn(OH) with a particle size of 0.5 to 2 mm. 4-x F x / PVC-PVB small balls;
[0020] S5 Fluorine-chlorine replacement: using NaCl-NaHCO3 solution to Sn(OH) 4-x F x / PVC-PVB beads are subjected to fluorine-chlorine replacement to obtain spherical fluorine adsorbent.
[0021] Furthermore, the dropping speed of the NaF-Na2CO3 solution in step S1 is 10 to 50 L / h;
[0022] And / or, the oxidation in step S2 is carried out by aeration;
[0023] Preferably, the oxidation is carried out by aerating Sn(OH) at a rate of 10 to 30 L / min. 2-x F x Air is introduced into the slurry.
[0024] Furthermore, the drying temperature in step S3 is 50-80°C, and after drying, Sn(OH) 4-x F x The moisture content of the powder is less than 5%.
[0025] And / or, the solvent in step S4 is N,N-dimethylacetamide;
[0026] And / or, the mass of the solvent in step S4 is 75-150% of the total mass of the granulation raw material; the total mass of the granulation raw material is Sn(OH) 4-x F x The sum of the mass of powder, PVC and PVB;
[0027] And / or, the pH value of the NaCl-NaHCO3 solution in step S5 is 7.5-8.5.
[0028] Furthermore, in step S4, the mass of PVC and PVB accounts for 8-25% of the total mass of the granulation raw materials;
[0029] And / or, in step S4, the mass ratio of PVC to PVB is 1:1-5.
[0030] The present invention provides an application of the fluorine adsorbent in the treatment of fluorine-containing wastewater.
[0031] The present invention provides a method for treating fluorine-containing wastewater based on the above-mentioned fluorine adsorbent, the method comprising:
[0032] (A) Defluorination of wastewater;
[0033] (B) fluorine adsorbent regeneration;
[0034] (C) The regeneration liquid is reused.
[0035] Furthermore, the wastewater defluorination comprises: filling a fluorine adsorbent into an adsorption column, then flowing the fluorine-containing wastewater into the adsorption column for defluorination, and when the fluorine ion concentration is greater than 1 mg / L, stopping the flow of the fluorine-containing wastewater and regenerating the fluorine adsorbent;
[0036] And / or, the fluorine adsorbent regeneration includes: using MgCl2 solution as regeneration liquid to circulate and elute the fluorine adsorbent adsorbed with fluorine ions, completing the regeneration of the fluorine adsorbent, and obtaining an eluent containing MgCl2 solution and MgF2 precipitate;
[0037] Preferably, the concentration of the MgCl2 solution is 0.5-3 mol / L.
[0038] Further, the regeneration liquid reuse includes:
[0039] (C1) performing solid-liquid separation on the eluate containing the MgCl2 solution and the MgF2 precipitate to obtain a MgCl2 solution and a MgF2 precipitate;
[0040] (C2) adjusting the concentration of the MgCl2 solution to 0.5-3 mol / L for recycling as a regeneration solution;
[0041] And, the MgF2 precipitate is dried to obtain MgF2 powder.
[0042] Compared with the prior art, the present invention has the following beneficial effects:
[0043] The structural formula of the fluorine adsorbent provided by the present invention is: Sn(OH) 4-x Cl x / PVC-PVB, wherein: 0.8≤x≤1.0; the PVC-PVB is a dual binder, and the fluorine adsorbent is prepared by using PVC and PVB as binders. In the structural formula of the above fluorine adsorbent, Sn(OH) 4-x Cl xThe powder has stable physical and chemical structure and high adsorption capacity. At the same time, the soft and hard skeleton of the PVC-PVB dual binder can make the Sn(OH) 4-x Cl x / PVC-PVB adsorbent beads form an extensive adsorption channel, which greatly improves the adsorption capacity and adsorption stability of the fluorine adsorbent.
[0044] The invention provides a method for preparing a fluorine adsorbent, wherein the method uses NaF-Na2CO3 solution, SnCl2-citric acid solution and NaCl-NaHCO3 solution as raw materials, and carries out precipitation reaction, oxidation reaction, drying and pulverization, powder granulation and fluorine-chlorine replacement steps to prepare Sn(OH) 4-x Cl x / PVC-PVB fluorine adsorbent. The above preparation method has the advantages of simple synthesis process and easy operation.
[0045] The fluorine adsorbent provided by the invention can be widely used in the treatment process of fluorine-containing wastewater.
[0046] The fluorine-containing wastewater treatment method based on the above fluorine adsorbent not only has the advantages of large adsorption capacity and stable adsorption performance in the treatment process of fluorine-containing wastewater; at the same time, the adsorbent has high regeneration efficiency, and the high concentration of fluoride ions in the regeneration liquid can be harmlessly treated to obtain high value-added MgF2 powder. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0048] Figure 1 A schematic diagram of the preparation process of the fluorine adsorbent provided by the present invention;
[0049] Figure 2 This is a schematic diagram of the application process of the fluorine adsorbent of the present invention in the process of treating fluorine-containing wastewater;
[0050] Figure 3a This is a physical picture of the fluorine adsorbent pellet product prepared in Example 1 of the present invention;
[0051] Figure 3b This is a surface scanning electron microscope image of the fluorine adsorbent pellet product prepared in Example 1 of the present invention;
[0052] Figure 4Example 1 Fluorine adsorbent Sn(OH) provided for Application Example 1 of the present invention 3.2 Cl 0.8 / The regular curve diagram of the fluorine concentration of the influent and produced water during the defluorination operation of the PVC-PVB ball in real fluoride-containing groundwater;
[0053] Figure 5a This is a physical picture of the fluorine adsorbent pellet product prepared in Example 2 of the present invention;
[0054] Figure 5b This is a surface scanning electron microscope image of the fluorine adsorbent pellet product prepared in Example 2 of the present invention;
[0055] Figure 6 Example 2 Fluorine adsorbent Sn(OH) provided for Application Example 2 of the present invention 3.1 Cl 0.9 / The regular curve diagram of fluorine concentration in influent and outfluent water during the defluorination operation of PVC-PVB balls in real fluorine-containing industrial wastewater;
[0056] Figure 7a This is a physical picture of the fluorine adsorbent pellet product prepared in Example 3 of the present invention;
[0057] Figure 7b This is a surface scanning electron microscope image of the fluorine adsorbent pellet product prepared in Example 3 of the present invention;
[0058] Figure 8 Example 3 Fluorine adsorbent Sn(OH) provided for Application Example 3 of the present invention 3.0 Cl 1.0 / The regular curve diagram of fluorine concentration in influent and outfluent water during the defluorination operation of PVC-PVB balls in real fluorine-containing industrial wastewater. DETAILED DESCRIPTION
[0059] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0060] According to one aspect of the present invention, a fluorine adsorbent has a structural formula of: Sn(OH) 4-x Cl x / PVC-PVB, where: 0.8≤x≤1.0;
[0061] The PVC-PVB is a dual binder, and the fluorine adsorbent is prepared by using PVC and PVB as binders.
[0062] The structural formula of the fluorine adsorbent provided by the present invention is: Sn(OH) 4-x Cl x / PVC-PVB, wherein: 0.8≤x≤1.0; the PVC-PVB is a dual binder, and the fluorine adsorbent is prepared by using PVC and PVB as binders. In the structural formula of the above fluorine adsorbent, Sn(OH) 4-x Cl x The powder has the properties of stable physical and chemical structure and high adsorption capacity, and matches the soft and hard skeleton granulation method of PVC-PVB dual binder, which can make the Sn(OH) 4-x Cl x / PVC-PVB adsorbent beads form an extensive adsorption channel, which greatly improves the adsorption capacity and adsorption stability of the fluorine adsorbent.
[0063] In a preferred embodiment of the present invention, the fluorine adsorbent is a spherical structure, and the particle size of the fluorine adsorbent is 0.5 to 2 mm.
[0064] According to one aspect of the present invention, a method for preparing a fluorine adsorbent comprises:
[0065] S1 precipitation reaction: NaF-Na2CO3 solution is added dropwise to SnCl2-citric acid solution to perform precipitation reaction to obtain Sn(OH) 2-x F x Slurry;
[0066] S2 oxidation reaction: Sn(OH) 2-x F x The slurry is oxidized to make Sn(OH) 2-x F x Transformed to Sn(OH) 4-x F x , Sn(OH) 4-x F x Slurry;
[0067] S3 dry powder: Sn(OH) 4-x F x The slurry was filtered to obtain Sn(OH) 4-x F x The filter cake is then dried and crushed to obtain Sn(OH) with a particle size of 0.5 to 20 μm. 4-x F x Powder;
[0068] S4 powder granulation: Sn(OH) 4-x F x Powder, PVC and PVB are added to the solvent to obtain a granulation solution; then drop ball granulation is performed to obtain Sn(OH) with a particle size of 0.5 to 2 mm.4-x F x / PVC-PVB small balls;
[0069] S5 Fluorine-chlorine replacement: using NaCl-NaHCO3 solution to Sn(OH) 4-x F x / PVC-PVB beads are subjected to fluorine-chlorine replacement to obtain spherical fluorine adsorbent.
[0070] The invention provides a method for preparing a fluorine adsorbent, wherein the method uses NaF-Na2CO3 solution, SnCl2-citric acid solution and NaCl-NaHCO3 solution as raw materials, and carries out precipitation reaction, oxidation reaction, drying and pulverization, powder granulation and fluorine-chlorine replacement steps to prepare Sn(OH) 4-x Cl x / PVC-PVB fluorine adsorbent. The above preparation method has the advantages of simple synthesis process and easy operation. The fluorine adsorbent prepared by this method not only has the performance of stable physical and chemical structure and high adsorption capacity, but also the soft and hard skeleton granulation method of PVC-PVB dual binder makes Sn(OH) 4-x Cl x / PVC-PVB beads form an extensive adsorption channel, which greatly improves the adsorption capacity and adsorption stability of the fluorine adsorbent.
[0071] Figure 1 This is a schematic diagram of the preparation process of the fluorine adsorbent provided by the present invention.
[0072] See also Figure 1 The preparation method of the fluorine adsorbent of the present application can be described as follows:
[0073] (I) Solution preparation:
[0074] 1. Preparation of SnCl2-citric acid solution: Add a certain mass of deionized water into a stirring tank, then add citric acid powder to prepare a citric acid solution with a mass fraction of 40%-60%, and then add SnCl2·2H2O powder to the citric acid solution so that the concentration of SnCl2 in the prepared SnCl2-citric acid solution is 1-2.5 mol / L to obtain a SnCl2-citric acid solution for standby use.
[0075] 2. Preparation of NaF-Na2CO3 solution: Add Na2CO3 powder to deionized water to prepare a saturated Na2CO3 solution, and then add NaF powder to the saturated Na2CO3 solution so that the concentration of NaF in the prepared NaF-Na2CO3 solution is 0.1-0.25 mol / L to obtain a NaF-Na2CO3 solution for later use.
[0076] 3. Preparation of NaCl-NaHCO3 solution: Add NaCl powder to deionized water to prepare 1-4 mol / L NaCl solution, then add NaHCO3 powder to the 1-4 mol / L NaCl solution, adjust the pH of the NaCl-NaHCO3 solution to 7.5-8.5, and obtain a NaCl-NaHCO3 solution for later use.
[0077] (II) Precipitation reaction:
[0078] In an enameled stirring tank, add 50-100L of SnCl2-citric acid solution and heat the solution to 50-90°C. Then, at a speed of 100-300rpm, add the above-prepared NaF-Na2CO3 solution to the enameled kettle at a dripping speed of 10-50L / h. The dripping volume of the NaF-Na2CO3 solution is 75-150L. After the reaction, Sn(OH) 2-x F x White slurry.
[0079] The reaction equation in this process is: 3SnCl2+3xNaF+(6-3x)Na2CO3+(2-x)C3H4OH(COOH)3=3Sn(OH) 2-x F x +6NaCl+(6-3x)CO2+(2-x)C3H4OH(COONa)3.
[0080] It should be noted that in the above precipitation reaction process, the NaF-Na2CO3 solution needs to be added dropwise to the SnCl2-citric acid solution, but the SnCl2-citric acid solution cannot be added dropwise to the NaF-Na2CO3 solution. This is because when the SnCl2-citric acid is excessive, the OH in the reaction solution will - Very little, OH - Unable to communicate with Sn 2+ The reaction takes place, and the F in the added NaF-Na2CO3 solution - It will quickly and Sn 2+ The complexation reaction first forms [SnF a ] 2-a Complex ions; With the addition of NaF-Na2CO3 solution, the pH value of SnCl2-citric acid solution becomes higher and higher, OH - As the concentration increases, [SnF a ] 2-a The complex ions begin to react with OH in the solution - React to generate Sn(OH) 2-x F x White precipitate.
[0081] In addition, it should be emphasized that during the above precipitation reaction, the target Sn(OH) 2-x F x The synthesis of - and Sn 2+ The fluoride ion F - Smoothly introduced into Sn-containing 2+ In a compound system, under weak acidic or weak alkaline conditions, the hydroxide OH - Introduced into Sn 2+ In the compound system, the reaction is carried out in two steps to avoid F - With OH - Competition for Sn 2+ The target Sn(OH) 2-x F x This is a major improvement of the present application over the prior art.
[0082] (III) Oxidation reaction:
[0083] At a speed of 100-300rpm, insert the aeration tube into the above slurry and aerate Sn(OH) at a rate of 10-30L / min. 2-x F x Air is introduced into the white slurry, and oxygen in the air is used as a cheap and readily available oxidant to make Sn(OH) 2-x F x White slurry turns into Sn(OH) 4-x F x Light yellow slurry.
[0084] The reaction equation in this process is: 2Sn(OH) 2-x F x +O2+2H2O=2Sn(OH) 4-x F x .
[0085] (IV) Drying and powdering:
[0086] The Sn(OH) 4-x F x The light yellow slurry is pumped into a plate-and-frame filter press to filter out the liquid to obtain Sn(OH) 4-x F x Light yellow filter cake; Sn(OH) 4-x F x The light yellow filter cake is placed in a crawler drying kiln, the temperature is controlled at 50-80°C, and dried to a moisture content of <5% to obtain Sn(OH) 4-x F x Light yellow dry solid block; Sn(OH)4-x F x The light yellow dry block solid was crushed by impact mill to obtain Sn(OH) with a particle size of 0.5-20 μm. 4-x F x Light yellow dry powder.
[0087] (V) Powder granulation:
[0088] Sn(OH) with a particle size of 0.5-20 μm 4-x F x Light yellow dry powder, polyvinyl chloride (PVC), polyvinyl butyral (PVB), and N,N-dimethylacetamide (DMAC) are mixed in a certain mass ratio, wherein:
[0089] The total mass of binder PVC and binder PVB accounts for the total powder mass (Sn(OH) 4-x F x +PVC+PVB) 8%-25%, the mass of solvent DMAC accounts for the total powder mass (Sn(OH) 4-x F x +PVC+PVB), and the mass ratio of the adhesive PVC to the adhesive PVB is 1:1-1:5.
[0090] Add the materials to the stirring kettle in this order: first add the solvent DMAC, heat to 50-90°C, add the binder PVC and the binder PVB while stirring, and after the binder PVC and the binder PVB are dissolved, add Sn(OH) 4-x F x Light yellow dry powder, continue stirring for 1-4h. Transfer the liquid to the ball dropping device for ball dropping, and the small ball falls into deionized water for phase conversion to obtain Sn(OH) with a particle size of 0.5-2mm 4-x F x / PVC-PVB small balls.
[0091] It should be noted that in the molding process of the powder of the present application, PVC and PVB are used as joint binders, wherein: the skeleton of PVC is a rigid skeleton, and the particles after molding are relatively hard, which is conducive to improving the Sn(OH) 4-x F x / PVC-PVB ball has high pressure and wear resistance; the skeleton of PVB is flexible and the particles after molding are relatively soft, which is beneficial to Sn(OH) 4-x F x Powder entanglement and interception to avoid Sn(OH) 4-x F x / Loss of effective powder in PVC-PVB balls;
[0092] In addition, the chemical formula of the above PVB (C8H 14 O2) n There are a lot of oxygen atoms in it, which can react with Sn(OH) 4-x F x The hydrogen atoms in the powder form hydrogen bonds, which are beneficial to the mutual traction between the powder and the organic skeleton, and are beneficial to the uniform dispersion and stable attraction of the powder, thus avoiding the loss of the powder.
[0093] (VI) Fluorine-chlorine replacement:
[0094] 100-200L of Sn(OH) 4-x F x / PVC-PVB balls are loaded in the adsorption column, and the above-prepared NaCl-NaHCO3 solution with a pH of 7.5-8.5 is added from the bottom of the adsorption column at a flow rate of 1-3BV / h. The amount of NaCl-NaHCO3 solution used is 150-300L to fully soak the Sn(OH) 4-x F x / PVC-PVB small balls, making Sn(OH) 4-x F x / The fluorine element on the PVC-PVB ball is replaced by the chlorine element in the NaCl--NaHCO3 solution, Sn(OH) 4-x F x / PVC-PVB beads transformed into Sn(OH) 4-x Cl x / PVC-PVB small balls.
[0095] The ion exchange reaction that occurs in this process is: Sn(OH) 4-x F x / PVC-PVB+xNaCl=Sn(OH) 4-x Cl x / PVC-PVB+xNaF. Sn(OH) 4-x Cl x / PVC-PVB beads are the prepared fluorine adsorbent.
[0096] It should be emphasized that in the fluorine-chlorine replacement process of the present application, a NaCl-NaHCO3 solution with a pH of 7.5-8.5 is used instead of a pure NaCl solution. That is, the fluorine-chlorine replacement process of the present application utilizes the appropriate concentration of hydroxide OH in the weak alkaline solution. - Sn(OH) 4-x F x The Sn-F chemical bond on the - Concentration (≈10 - 4mol / L) and the Cl of NaCl-NaHCO3 solution - Compared with the concentration (1~4mol / L), OH - The concentration is at an extremely low concentration, so after the Sn-F chemical bond breaks, a Sn-Cl chemical bond is formed instead of a Sn-OH chemical bond, achieving fluorine-chlorine replacement and obtaining the effective component of the fluorine adsorbent, Sn(OH) 4-x Cl x This is also a major innovation of this application relative to the prior art.
[0097] According to one aspect of the present invention, the above-mentioned fluorine adsorbent is used in the treatment of fluorine-containing wastewater.
[0098] The fluorine adsorbent provided by the present invention can be widely used in the treatment process of fluorine-containing wastewater. The above-mentioned fluorine adsorbent not only has the advantages of large adsorption capacity, stable adsorption performance, high regeneration efficiency, and high concentration of fluorine ions in the regeneration liquid can be efficiently and harmlessly treated in the treatment process of fluorine-containing wastewater, but also the MgF2 precipitate formed in the regeneration process is a useful material with high added value.
[0099] Therefore, the treatment process of the fluorine adsorbent of the present invention can convert the toxic and harmful fluorine ions exceeding the standard in sewage into MgF2 powder which can be sold, has high added value and is widely used, thus truly turning waste into treasure and making efficient use of resources.
[0100] According to one aspect of the present invention, a method for treating fluorine-containing wastewater based on the above-mentioned fluorine adsorbent comprises:
[0101] (A) Defluorination of wastewater;
[0102] (B) fluorine adsorbent regeneration;
[0103] (C) The regeneration liquid is reused.
[0104] Figure 2 The figure is a schematic diagram of the application process of the fluorine adsorbent of the present invention in the treatment process of fluorine-containing wastewater.
[0105] See also Figure 2 The present invention relates to a method for treating fluorine-containing wastewater based on the above-mentioned fluorine adsorbent, which can be described as follows:
[0106] (A) Wastewater defluorination process:
[0107] Sn(OH) 4-x Cl x / PVC-PVB balls are loaded in the adsorption column. The fluoride ion concentration of the fluoride-containing wastewater is 5-200 mg / L. The fluoride-containing wastewater flows into the adsorption column from bottom to top at a flow rate of 5-20BV. The fluoride ion concentration in the produced water after fluoride removal is less than 1 mg / L.
[0108] The ionic equation for the defluorination process is: Sn(OH) 4-x Cl x / PVC-PVB+xF - =Sn(OH) 4-x F x / PVC-PVB+xCl - .
[0109] Preferably, a fluoride ion sensor is installed at the water outlet to monitor the fluoride ion concentration of the produced water in real time online. Once the fluoride ion concentration of the produced water is greater than 1 mg / L, adsorption of the incoming water is stopped to prepare for regeneration.
[0110] (B) Fluorine adsorbent regeneration process:
[0111] When the fluoride ion concentration of the adsorption column of the fluorine adsorbent is greater than 1mg / L, the 0.5-3mol / L MgCl2 solution in the regeneration liquid storage tank A is used as the regeneration liquid, and the fluorine adsorbent is regenerated from bottom to top at a flow rate of 15-25BV / h. The regeneration liquid storage tank A and the adsorption column are used as a circulation system, and the upper water of the adsorption column is returned to the regeneration liquid storage tank A. The volume of the regeneration liquid is 2-4BV, and the circulation is 10-20min to complete the regeneration of the fluorine adsorbent. After the regeneration is completed, all the residual regeneration liquid in the adsorption column is pumped back to the regeneration liquid storage tank A.
[0112] The ionic equation for the regeneration process is: Sn(OH) 4-x F x / PVC-PVB+xCl - =Sn(OH) 4-x Cl x / PVC-PVB+xF - Mg 2+ +2F - =MgF2↓. During the regeneration process of the fluorine adsorbent, magnesium ions Mg 2+ will react with the eluted fluoride ion F - The precipitation reaction is carried out to quickly reduce the concentration of fluoride ions in the regeneration liquid, prevent the fluoride adsorbent from continuing to adsorb fluoride ions in the regeneration liquid, facilitate the elution of fluoride ions on the fluoride adsorbent, and realize a fast and efficient regeneration process.
[0113] It should be noted that, using MgCl2 solution as the regeneration solution, magnesium ions and fluoride ions can form precipitated MgF2. 2+ +2F - = The presence of MgF2↓, a large amount of Mg in the regeneration solution 2+ , which can induce Sn(OH) 4-x F x / The Sn-F chemical bond on the PVC-PVB ball breaks, and after the Sn-F chemical bond breaks, the Sn-Cl chemical bond is immediately formed. However, since the bond energy of the Sn-Cl chemical bond is lower than that of the Sn-F chemical bond, the tendency of forming the Sn-F chemical bond is higher than that of forming the Sn-Cl chemical bond. Once the concentration of fluoride ions resolved in the regeneration liquid increases, the regeneration process will show a reverse adsorption phenomenon, that is, the fluoride ions in the regeneration liquid will be re-adsorbed onto the fluoride adsorbent.
[0114] The present application uses 0.5-3 mol / L MgCl2 solution as the regeneration liquid, which solves this problem. Because the fluoride ions in the regeneration liquid will undergo precipitation reaction with the magnesium ions in the regeneration liquid, the fluoride ion concentration in the regeneration liquid is greatly reduced, the regeneration rate and regeneration time are improved, and the regeneration of the fluoride adsorbent can be completed in only 10-20 minutes.
[0115] It should also be noted that, in the regeneration process of the fluorine adsorbent of the present invention, the fluorine adsorbent is regenerated from bottom to top at a flow rate of 15-25BV / h, and the regeneration liquid storage tank A and the adsorption column are used as a circulation system. The innovation of this step relative to the prior art is that the regeneration liquid is pumped into the adsorption column at a high flow rate, which is conducive to breaking up the formed MgF2 precipitate to form extremely small particles of precipitation, avoiding the formation of large flocculent precipitation, and the high flow rate is conducive to preventing the precipitate from being deposited on the Sn(OH) 4-x Cl x / PVC-PVB balls are placed on the surface to avoid clogging the adsorption channel and adsorption site; in addition, the regeneration liquid storage tank A and the adsorption column are regenerated as a circulation system instead of a one-time over-flow regeneration, which is beneficial to reduce the amount of regeneration liquid, reduce the volume of the liquid storage tank, reduce the floor space, and facilitate engineering applications.
[0116] (C) Regeneration liquid reuse process: After the fluorine adsorbent is regenerated by the regeneration liquid (0.5-3 mol / L MgCl2 solution), an eluent (a mixture of MgCl2 solution and MgF2 precipitate, wherein the MgCl2 concentration is less than 0.5-3 mol / L) is obtained, and the eluent is pumped into a plate and frame filter press to perform solid-liquid separation of the MgCl2 solution and the MgF2 precipitate to obtain a MgCl2 solution (filtrate) and a MgF2 filter cake.
[0117] The MgCl2 solution (filtrate) is pumped back to the regeneration liquid storage tank B. After all the eluent in the regeneration liquid storage tank A has flowed through the plate and frame filter press, the slightly lower concentration MgCl2 solution (filtrate) in the regeneration liquid storage tank B is pumped into the regeneration liquid storage tank A, and an appropriate amount of MgCl2·6H2O solid is added to the regeneration liquid storage tank A to obtain a 0.5-3 mol / L MgCl2 solution as a new regeneration liquid for recycling.
[0118] After the MgF2 filter cake is dried and crushed, MgF2 powder is obtained, which can be sold as a chemical. As an important inorganic compound, magnesium fluoride has shown wide application potential and unlimited possibilities in the electronics industry. Its excellent physical and chemical properties make it a key material in high-power and high-frequency electronic devices, chip manufacturing, solar cells and other fields.
[0119] It should be noted that the present application adopts a plate and frame filter press for solid-liquid separation of MgCl2 solution and MgF2 precipitate, which is more efficient and energy-saving than centrifugation or evaporation, and is more conducive to continuous operation; at the same time, in addition to the reuse of the MgCl2 solution (filtrate) during the above-mentioned regeneration liquid reuse process, a high-value-added MgF2 powder can also be obtained. The powder has a wide range of uses and high added value. It can be widely used in the optical field, the electronics industry, the photovoltaic field, the raw materials of ion conductive materials and electronic devices, the manufacture of high-power electronic devices and integrated circuits, catalyst carriers, the biomedical field, bulletproof and protective materials, metallurgical industry, ceramics and glass industries, and nuclear energy and many other fields.
[0120] The technical solution of the present invention will be further described below in conjunction with embodiments.
[0121] Example 1
[0122] A method for preparing a fluorine adsorbent, the method comprising:
[0123] (i) Solution preparation: Preparation of SnCl2-citric acid solution: Add a certain mass of deionized water into a stirring tank, then add citric acid powder to prepare a citric acid solution with a mass fraction of 40%, and then add SnCl2·2H2O powder to the citric acid solution so that the concentration of SnCl2 in the prepared SnCl2-citric acid solution is 1 mol / L, thereby obtaining a SnCl2-citric acid solution.
[0124] Preparation of NaF-Na2CO3 solution: Na2CO3 powder is added to deionized water to prepare a saturated Na2CO3 solution, and then NaF powder is added to the saturated Na2CO3 solution so that the concentration of NaF in the prepared NaF-Na2CO3 solution is 0.1 mol / L to obtain a NaF-Na2CO3 solution.
[0125] Preparation of NaCl-NaHCO3 solution: Add NaCl powder to deionized water to prepare 1 mol / L NaCl solution, then add NaHCO3 powder to the 1 mol / L NaCl solution, adjust the pH of the NaCl-NaHCO3 solution to 7.5, and obtain a NaCl-NaHCO3 solution.
[0126] (ii) Precipitation reaction: Add 50L of SnCl2-citric acid solution to an enameled stirring tank and heat the solution to 50°C. Then, add the prepared NaF-Na2CO3 solution to the enameled kettle at a dripping rate of 10L / h at a speed of 100rpm. The dripping volume of the NaF-Na2CO3 solution is 75L. After the reaction, Sn(OH) 2-x F x White slurry.
[0127] (III) Oxidation reaction: At a speed of 100 rpm, insert the aeration tube into the above slurry and aerate Sn(OH) at a rate of 10 L / min. 2-x F x Air is introduced into the white slurry, and oxygen in the air is used as a cheap and readily available oxidant to make Sn(OH) 2-x F x White slurry turns into Sn(OH) 4-x F x Light yellow slurry.
[0128] (IV) Drying and pulverizing: Sn(OH) 4-x F x The light yellow slurry is pumped into a plate-and-frame filter press to filter out the liquid to obtain Sn(OH) 4-x F x Light yellow filter cake; Sn(OH) 4-x F x The light yellow filter cake was placed in a crawler drying kiln, the temperature was controlled at 50°C, and dried to a moisture content of 1% to obtain Sn(OH) 4-x F x Light yellow dry solid block; Sn(OH) 4-x F x The light yellow dry block solid was crushed by impact mill to obtain Sn(OH) with a particle size of 0.5-5 μm. 4-x F x Light yellow dry powder.
[0129] (V) Powder granulation: Sn(OH) with a particle size of 0.5-5μm 4-x F x Light yellow dry powder, polyvinyl chloride (PVC), polyvinyl butyral (PVB), and N,N-dimethylacetamide (DMAC) are mixed in a certain mass ratio, wherein the total mass of the binder PVC and the binder PVB accounts for 1.3% of the total powder mass (Sn(OH) 4-x F x +PVC+PVB), the mass of solvent DMAC accounts for 8% of the total powder mass (Sn(OH) 4-x F x+PVC+PVB), and the mass ratio of the adhesive PVC to the adhesive PVB is 1:1.
[0130] Add the materials to the stirring tank in this order: first add the solvent DMAC, heat to 50°C, add the binder PVC and the binder PVB while stirring, and after the binder PVC and the binder PVB are dissolved, add Sn(OH) 4-x F x Light yellow dry powder, continue stirring for 1h. Transfer the liquid to the ball dropping device for ball dropping, and the small ball falls into deionized water for phase conversion to obtain Sn(OH) with a particle size of 0.5mm 4-x F x / PVC-PVB small balls.
[0131] (VI) Fluorine-chlorine replacement: 100L of Sn(OH) 4-x F x / PVC-PVB balls were loaded into the adsorption column, and the above-prepared NaCl-NaHCO3 solution with a pH of 7.5 was added from the bottom of the adsorption column at a flow rate of 1BV / h. The amount of NaCl-NaHCO3 solution was 150L, and the Sn(OH) 4-x F x / PVC-PVB small balls, making Sn(OH) 4-x F x / The fluorine element on the PVC-PVB ball is replaced by the chlorine element in the NaCl--NaHCO3 solution, Sn(OH) 4-x F x / PVC-PVB beads transformed into Sn(OH) 4-x Cl x / PVC-PVB small balls.
[0132] (VII) Fluorine adsorbent property detection:
[0133] Figure 3a This is a physical picture of the fluorine adsorbent bead product prepared in this example.
[0134] Figure 3b This is a surface scanning electron microscope image of the fluorine adsorbent bead product prepared in this example.
[0135] from Figure 3a , Figure 3b It can be seen from the figure that the particle size of the fluorine adsorbent beads is very uniform, about 0.5 mm in size, and the fluorine adsorbent powder is wrapped by PVC and PVB resin to prevent the fluorine adsorbent powder from falling off. In addition, it can be seen from the figure that PVC and PVB resin form a rich pore structure, and the interconnected network pore structure is conducive to the adsorption and elution of fluorine ions, thereby improving the ion exchange efficiency.
[0136] Table 1 is the fluorine adsorbent Sn(OH) prepared in this example 4-x Cl x / PVC-PVB small ball products are produced by heating and dissolving Sn(OH) with 4 mol / L sodium hydroxide 4-x Cl x After that, the contents of Sn and Cl in the solution were tested with instruments, and it was deduced that Sn(OH) 4-x Cl x The chemical formula is Sn(OH) 3.2 Cl 0.8 .
[0137] Table 1 Chemical formula and adsorption capacity analysis of fluorine adsorbent of Example 1:
[0138]
[0139] Tested Sn(OH) 3.2 Cl 0.8 The saturated adsorption capacity of fluoride ions of the PVC-PVB beads is 115 mg / g, which is much higher than the 31 mg / g of the fluoride adsorbent (TFR-93) on the market. 3.2 Cl 0.8 / PVC-PVB beads have the performance advantage of high adsorption capacity. In addition, Sn(OH) 3.2 Cl 0.8 The powder loss rate of the PVC-PVB ball after 1000 cycles is only 0.5%, proving that the soft and hard skeleton of the PVC-PVB dual binder can make the Sn(OH) 4- x Cl x / PVC-PVB adsorbent beads form an extensive adsorption channel, while also avoiding Sn(OH) 3.2 Cl 0.8 / The loss of effective powder in the PVC-PVB beads greatly improves the adsorption capacity and adsorption stability of the fluorine adsorbent.
[0140] Application Example 1
[0141] The fluorine adsorbent Sn(OH) prepared in Example 1 was 3.2 Cl 0.8 / PVC-PVB balls were used for application tests.
[0142] See also Figure 2 The schematic diagram of the application process of the fluorine adsorbent of the present invention in the process of treating fluorine-containing wastewater is shown in the following figure. The application process of the fluorine adsorbent in this application example based on Example 1 for treating fluorine-containing wastewater includes:
[0143] (1) Wastewater defluorination process: The fluorine adsorbent beads prepared in Example 1 were loaded into an adsorption column. The fluorine ion concentration of the fluorine-containing wastewater was 5 mg / L. The fluorine-containing wastewater flowed into the adsorption column from bottom to top at a flow rate of 5 BV. The fluorine ion concentration in the produced water after defluorination was less than 1 mg / L.
[0144] A fluoride ion sensor is installed at the water outlet to monitor the fluoride ion concentration of the produced water in real time online. Once the fluoride ion concentration of the produced water is greater than 1 mg / L, the adsorption of water will be stopped and regeneration will be prepared.
[0145] (2) Fluorine adsorbent regeneration process: When the fluorine ion concentration of the adsorption column of the fluorine adsorbent is greater than 1mg / L, the 0.5mol / L MgCl2 solution in the regeneration liquid storage tank A is used as the regeneration liquid to regenerate the fluorine adsorbent from bottom to top at a flow rate of 15BV / h. The regeneration liquid storage tank A and the adsorption column are used as a circulation system. The upper water of the adsorption column is returned to the regeneration liquid storage tank A. The regeneration liquid volume is 2BV. The circulation is 10 minutes to complete the regeneration of the fluorine adsorbent. After the regeneration is completed, all the residual regeneration liquid in the adsorption column is pumped back to the regeneration liquid storage tank A.
[0146] (3) Regeneration liquid reuse process: After the regeneration liquid (0.5 mol / L MgCl2 solution) regenerates the fluorine adsorbent, an eluent (a mixture of MgCl2 solution and MgF2 precipitate, wherein the MgCl2 concentration is less than 0.5 mol / L) is obtained, and the eluent is pumped into a plate-frame filter press to perform solid-liquid separation of the MgCl2 solution and the MgF2 precipitate, and the MgCl2 solution (filtrate) is pumped back to the regeneration liquid storage tank B. After the eluent in the regeneration liquid storage tank A has all flowed through the plate-frame filter press, the MgCl2 solution (filtrate) with a slightly lower concentration in the regeneration liquid storage tank B is pumped into the regeneration liquid storage tank A, and an appropriate amount of MgCl2·6H2O solid is added to the regeneration liquid storage tank A to obtain a 0.5 mol / L MgCl2 solution that is used as a new regeneration liquid for recycling. The MgF2 filter cake is dried and crushed to obtain MgF2 powder, which can be sold as a chemical.
[0147] Figure 4 Example 1 fluorine adsorbent Sn(OH) provided for this application example 3.2 Cl 0.8 / The regular curve diagram of fluoride concentration in influent and produced water during the defluorination operation of PVC-PVB balls in real fluoride-containing groundwater.
[0148] from Figure 4It can be seen that the fluoride ion concentration of the produced water of the fluoride adsorbent during the defluorination process is very stable. The fluoride ion concentration in the fluoride-containing groundwater inlet is about 5 mg / L. Before the column adsorption is saturated, the fluoride ion concentration of the produced water is always <0.5 mg / L. China's "Sanitary Standards for Drinking Water" (GB5749-2022) stipulates that the limit value of fluoride in drinking water is 1.0 mg / L, which proves that the fluoride adsorbent can meet the national standard requirements for groundwater defluorination and engineering needs, and has the advantages of large adsorption capacity and stable adsorption performance, and is expected to be able to be applied on a large scale. In addition, the purity of the MgF2 powder product obtained by the application method of the above-mentioned fluoride adsorbent for defluorination of fluoride-containing groundwater is 99.6%, which can be sold as a high value-added product. It proves that the fluoride adsorbent can realize the resource utilization of sewage and turn waste into treasure.
[0149] Example 2
[0150] A method for preparing a fluorine adsorbent, the method comprising:
[0151] (i) Solution preparation: Preparation of SnCl2-citric acid solution: Add a certain mass of deionized water into a stirring tank, then add citric acid powder to prepare a citric acid solution with a mass fraction of 50%, and then add SnCl2·2H2O powder to the citric acid solution so that the concentration of SnCl2 in the prepared SnCl2-citric acid solution is 1.75 mol / L, thereby obtaining a SnCl2-citric acid solution.
[0152] Preparation of NaF-Na2CO3 solution: Na2CO3 powder is added to deionized water to prepare a saturated Na2CO3 solution, and then NaF powder is added to the saturated Na2CO3 solution so that the concentration of NaF in the prepared NaF-Na2CO3 solution is 0.175 mol / L to obtain a NaF-Na2CO3 solution.
[0153] Preparation of NaCl-NaHCO3 solution: Add NaCl powder to deionized water to prepare 2.5 mol / L NaCl solution, then add NaHCO3 powder to the 2.5 mol / L NaCl solution, adjust the pH of the NaCl-NaHCO3 solution to 8, and obtain a NaCl-NaHCO3 solution.
[0154] (ii) Precipitation reaction: Add 75L of SnCl2-citric acid solution to an enameled stirring tank and heat the solution to 70°C. Then, add the prepared NaF-Na2CO3 solution to the enameled kettle at a dripping rate of 30L / h at a speed of 200rpm. The dripping volume of the NaF-Na2CO3 solution is 112.5L. After the reaction, Sn(OH) 2-x F x White slurry.
[0155] (III) Oxidation reaction: At a speed of 200 rpm, insert the aeration tube into the above slurry and aerate Sn(OH) at a rate of 20 L / min. 2-x F x Air is introduced into the white slurry, and oxygen in the air is used as a cheap and readily available oxidant to make Sn(OH) 2-x F x White slurry turns into Sn(OH) 4-x F x Light yellow slurry.
[0156] (IV) Drying and pulverizing: Sn(OH) 4-x F x The light yellow slurry is pumped into a plate-and-frame filter press to filter out the liquid to obtain Sn(OH) 4-x F x Light yellow filter cake; Sn(OH) 4-x F x The light yellow filter cake was placed in a crawler drying kiln, the temperature was controlled at 65°C, and dried to a moisture content of 2.5% to obtain Sn(OH) 4-x F x Light yellow dry solid block; Sn(OH) 4-x F x The light yellow dry block solid was crushed by impact mill to obtain Sn(OH) with a particle size of 0.5-10 μm. 4-x F x Light yellow dry powder.
[0157] (V) Powder granulation: Sn(OH) with a particle size of 0.5-10μm 4-x F x Light yellow dry powder, polyvinyl chloride (PVC), polyvinyl butyral (PVB), and N,N-dimethylacetamide (DMAC) are mixed in a certain mass ratio, wherein the total mass of the binder PVC and the binder PVB accounts for 1% of the total powder mass (Sn(OH) 4-x F x +PVC+PVB) accounts for 16.5% of the total powder mass (Sn(OH) 4-x F x +PVC+PVB) is 112.5%, and the mass ratio of the adhesive PVC to the adhesive PVB is 1:3.
[0158] Add the materials to the stirring tank in this order: first add the solvent DMAC, heat to 70°C, add the binder PVC and the binder PVB while stirring, and after the binder PVC and the binder PVB are dissolved, add Sn(OH) 4-x F xLight yellow dry powder, continue stirring for 2.5h. Transfer the liquid to the ball dropping device for ball dropping, and the small ball falls into deionized water for phase conversion to obtain Sn(OH) with a particle size of about 1mm 4-x F x / PVC-PVB small balls.
[0159] (VI) Fluorine-chlorine replacement: 150L of Sn(OH) 4-x F x / PVC-PVB balls were loaded into the adsorption column, and the pH 8 NaCl-NaHCO3 solution prepared above was added from the bottom of the adsorption column at a flow rate of 2BV / h. The amount of NaCl-NaHCO3 solution used was 225L, and Sn(OH) was fully soaked. 4-x F x / PVC-PVB small balls, making Sn(OH) 4-x F x / The fluorine element on the PVC-PVB ball is replaced by the chlorine element in the NaCl--NaHCO3 solution, Sn(OH) 4-x F x / PVC-PVB beads transformed into Sn(OH) 4-x Cl x / PVC-PVB small balls, Sn(OH) 4-x Cl x / PVC-PVB beads are the prepared fluorine adsorbent.
[0160] (VII) Fluorine adsorbent property detection:
[0161] Figure 5a This is a physical picture of the fluorine adsorbent bead product prepared in this example.
[0162] Figure 5b This is a surface scanning electron microscope image of the fluorine adsorbent bead product prepared in this example.
[0163] from Figure 5a , Figure 5b It can be seen that the particle size of the fluorine adsorbent beads is very uniform, about 1 mm in size, and the fluorine adsorbent powder is wrapped by PVC and PVB resin to prevent the fluorine adsorbent powder from falling off. Figure 5a , Figure 5b It can be seen that PVC and PVB resins form a rich pore structure, and the interconnected network pore structure is conducive to the adsorption and elution of fluoride ions, thereby improving the ion exchange efficiency.
[0164] Table 2 is the fluorine adsorbent Sn(OH) prepared in this example 4-x Cl x / PVC-PVB small ball products are produced by heating and dissolving Sn(OH) with 4 mol / L sodium hydroxide 4-x Cl x After that, the contents of Sn and Cl in the solution were tested with instruments, and it was deduced that Sn(OH) 4-x Cl x The chemical formula is Sn(OH) 3.1 Cl 0.9 .
[0165] Table 2 Chemical formula and adsorption capacity analysis of fluorine adsorbent in Example 2:
[0166]
[0167] Tested Sn(OH) 3.1 Cl 0.9 The saturated adsorption capacity of fluoride ions of the PVC-PVB beads is 139 mg / g, which is much higher than the 31 mg / g of the fluoride adsorbent (TFR-93) on the market. 3.1 Cl 0.9 / PVC-PVB beads have the performance advantage of high adsorption capacity. In addition, Sn(OH) 3.1 Cl 0.9 The powder loss rate of the PVC-PVB ball after 1000 cycles is only 0.42%, proving that the soft and hard skeleton of the PVC-PVB dual binder can make the Sn(OH) 3.1 Cl 0.9 / PVC-PVB adsorbent beads form an extensive adsorption channel, while also avoiding Sn(OH) 3.1 Cl 0.9 / The loss of effective powder in the PVC-PVB beads greatly improves the adsorption capacity and adsorption stability of the fluorine adsorbent.
[0168] Application Example 2
[0169] The fluorine adsorbent Sn(OH) prepared in Example 2 was 3.1 Cl 0.9 / PVC-PVB balls were used for application tests.
[0170] See also Figure 2 The fluorine-containing wastewater treatment application process based on the fluorine adsorbent of Example 2 includes:
[0171] (1) Wastewater defluorination process: The fluorine adsorbent beads prepared in Example 2 are loaded into the adsorption column. The fluorine ion concentration of the fluorine-containing industrial wastewater is about 100 mg / L. The fluorine-containing wastewater flows into the adsorption column from bottom to top at a flow rate of 12.5 BV. The fluorine ion concentration in the produced water after defluorination is less than 1 mg / L. A fluorine ion sensor is installed at the water outlet to monitor the fluorine ion concentration of the produced water in real time online. Once the fluorine ion concentration of the produced water is greater than 1 mg / L, the adsorption of the water is stopped and regeneration is prepared.
[0172] (2) Fluorine adsorbent regeneration process: When the fluorine ion concentration of the adsorption column of the fluorine adsorbent is greater than 1mg / L, the 1.75mol / L MgCl2 solution in the regeneration liquid storage tank A is used as the regeneration liquid to regenerate the fluorine adsorbent from bottom to top at a flow rate of 20BV / h. The regeneration liquid storage tank A and the adsorption column are used as a circulation system. The upper water of the adsorption column is returned to the regeneration liquid storage tank A. The regeneration liquid volume is 3BV. The circulation is 15 minutes to complete the regeneration of the fluorine adsorbent. After the regeneration is completed, all the residual regeneration liquid in the adsorption column is pumped back to the regeneration liquid storage tank A.
[0173] (3) Regeneration liquid reuse process: After the regeneration liquid (1.75 mol / L MgCl2 solution) regenerates the fluorine adsorbent, an eluent (a mixture of MgCl2 solution and MgF2 precipitate, wherein the MgCl2 concentration is less than 1.75 mol / L) is obtained, and the eluent is pumped into a plate-frame filter press to perform solid-liquid separation of the MgCl2 solution and the MgF2 precipitate, and the MgCl2 solution (filtrate) is pumped back to the regeneration liquid storage tank B. After the eluent in the regeneration liquid storage tank A has all flowed through the plate-frame filter press, the MgCl2 solution (filtrate) with a slightly lower concentration in the regeneration liquid storage tank B is pumped into the regeneration liquid storage tank A, and an appropriate amount of MgCl2·6H2O solid is added to the regeneration liquid storage tank A to obtain a 1.75 mol / L MgCl2 solution that is used as a new regeneration liquid for recycling. The MgF2 filter cake is dried and crushed to obtain MgF2 powder, which can be sold as a chemical.
[0174] Figure 6 Example 2 Fluorine adsorbent Sn(OH) provided for this application example 3.1 Cl 0.9 / The regular curve diagram of fluorine concentration in influent and outfluent water during the defluorination operation of PVC-PVB balls in real fluorine-containing industrial wastewater.
[0175] from Figure 6It can be seen that the fluoride ion concentration in the water produced by the fluoride adsorbent during the fluoride removal process is very stable. The fluoride ion concentration in the fluoride-containing groundwater inlet is about 100 mg / L, and the fluoride ion concentration in the water produced is always less than 0.5 mg / L before the column adsorption is saturated. China's "National Drinking Water Quality Standard" (GB5749-2022) stipulates that the limit value of fluoride in drinking water is 1.0 mg / L, which proves that the fluoride adsorbent can meet the national standard requirements for groundwater defluoridation and also meet engineering needs. It has the advantages of large adsorption capacity and stable adsorption performance, and is expected to be able to be applied on a large scale.
[0176] In addition, the purity of the MgF2 powder product obtained by using the above-mentioned fluorine adsorbent to remove fluorine from fluorine-containing groundwater is 99.8%, which can be sold as a high-value-added product. This proves that the fluorine adsorbent can realize the resource utilization of sewage and turn waste into treasure.
[0177] Example 3
[0178] A method for preparing a fluorine adsorbent, the method comprising:
[0179] (i) Solution preparation: Preparation of SnCl2-citric acid solution: Add a certain mass of deionized water into a stirring tank, then add citric acid powder to prepare a citric acid solution with a mass fraction of 60%, and then add SnCl2·2H2O powder to the citric acid solution so that the concentration of SnCl2 in the prepared SnCl2-citric acid solution is 2.5 mol / L, thereby obtaining a SnCl2-citric acid solution.
[0180] Preparation of NaF-Na2CO3 solution: Na2CO3 powder is added to deionized water to prepare a saturated Na2CO3 solution, and then NaF powder is added to the saturated Na2CO3 solution so that the concentration of NaF in the prepared NaF-Na2CO3 solution is 0.25 mol / L to obtain a NaF-Na2CO3 solution.
[0181] Preparation of NaCl-NaHCO3 solution: Add NaCl powder to deionized water to prepare 4 mol / L NaCl solution, then add NaHCO3 powder to the 4 mol / L NaCl solution, adjust the pH of the NaCl-NaHCO3 solution to 8.5, and obtain a NaCl-NaHCO3 solution.
[0182] (ii) Precipitation reaction: Add 100L of SnCl2-citric acid solution to an enameled stirring tank and heat the solution to 90°C. Then, add the above-prepared NaF-Na2CO3 solution to the enameled kettle at a dripping speed of 50L / h at a speed of 300rpm. The dripping volume of the NaF-Na2CO3 solution is 150L. After the reaction, Sn(OH) 2-x Fx White slurry.
[0183] (III) Oxidation reaction: At a speed of 300 rpm, insert the aeration tube into the above slurry and aerate Sn(OH) at a rate of 30 L / min. 2-x F x Air is introduced into the white slurry, and oxygen in the air is used as a cheap and readily available oxidant to make Sn(OH) 2-x F x White slurry turns into Sn(OH) 4-x F x Light yellow slurry.
[0184] (IV) Drying and pulverizing: Sn(OH) 4-x F x The light yellow slurry is pumped into a plate-and-frame filter press to filter out the liquid to obtain Sn(OH) 4-x F x Light yellow filter cake; Sn(OH) 4-x F x The light yellow filter cake was placed in a crawler drying kiln, the temperature was controlled at 80°C, and dried to a moisture content of 5% to obtain Sn(OH) 4-x F x Light yellow dry solid block; Sn(OH) 4-x F x The light yellow dry block solid was crushed by impact mill to obtain Sn(OH) with a particle size of 0.5-20 μm. 4-x F x Light yellow dry powder.
[0185] (V) Powder granulation: Sn(OH) with a particle size of 0.5-20 μm 4-x F x Light yellow dry powder, polyvinyl chloride (PVC), polyvinyl butyral (PVB), and N,N-dimethylacetamide (DMAC) are mixed in a certain mass ratio, wherein the total mass of the binder PVC and the binder PVB accounts for 1% of the total powder mass (Sn(OH) 4-x F x +PVC+PVB), the mass of solvent DMAC accounts for 25% of the total powder mass (Sn(OH) 4-x F x +PVC+PVB), and the mass ratio of the adhesive PVC to the adhesive PVB is 1:5.
[0186] Add the materials to the stirring kettle in this order: first add the solvent DMAC, heat to 90°C, add the binder PVC and the binder PVB while stirring, and after the binder PVC and the binder PVB are dissolved, add Sn(OH) 4-x Fx Light yellow dry powder, continue stirring for 4 hours. Transfer the liquid to the ball dropping device for ball dropping, and the small ball falls into deionized water for phase conversion to obtain Sn(OH) with a particle size of about 2 mm. 4-x F x / PVC-PVB small balls.
[0187] (VI) Fluorine-chlorine replacement: 200L of Sn(OH) 4-x F x / PVC-PVB balls were loaded into the adsorption column, and the above-prepared NaCl-NaHCO3 solution with a pH of 8.5 was added from the bottom of the adsorption column at a flow rate of 3BV / h. The amount of NaCl-NaHCO3 solution was 300L, and the Sn(OH) 4-x F x / PVC-PVB small balls, making Sn(OH) 4-x F x / The fluorine element on the PVC-PVB ball is replaced by the chlorine element in the NaCl--NaHCO3 solution, Sn(OH) 4-x F x / PVC-PVB beads transformed into Sn(OH) 4-x Cl x / PVC-PVB small balls, Sn(OH) 4-x Cl x / PVC-PVB beads are the prepared fluorine adsorbent.
[0188] (VII) Fluorine adsorbent property detection:
[0189] Figure 7a This is a physical picture of the fluorine adsorbent bead product prepared in this example.
[0190] Figure 7b This is a surface scanning electron microscope image of the fluorine adsorbent bead product prepared in this example.
[0191] from Figure 7a , Figure 7b It can be seen that the particle size of the fluorine adsorbent beads is very uniform, about 2 mm in size, and the fluorine adsorbent powder is wrapped by PVC and PVB resin to prevent the fluorine adsorbent powder from falling off. Figure 7a , Figure 7b It can be seen that PVC and PVB resins form a rich pore structure, and the interconnected network pore structure is conducive to the adsorption and elution of fluoride ions, thereby improving the ion exchange efficiency.
[0192] Table 3 is the fluorine adsorbent Sn(OH) prepared in this example 4-x Cl x / PVC-PVB small ball products are produced by heating and dissolving Sn(OH) with 4 mol / L sodium hydroxide 4-x Cl x After that, the contents of Sn and Cl in the solution were tested with instruments, and it was deduced that Sn(OH) 4-x Cl x The chemical formula is Sn(OH) 3.0 Cl 1.0 .
[0193] Table 3 Chemical formula and adsorption capacity analysis of fluorine adsorbent of Example 3:
[0194]
[0195]
[0196] Tested Sn(OH) 3.0 Cl 1.0 / PVC-PVB beads have a saturated adsorption capacity of fluoride ions of 162 mg / g, which is much higher than the 31 mg / g of the fluoride adsorbent (TFR-93) on the market. 3.0 Cl 1.0 / PVC-PVB beads have the performance advantage of high adsorption capacity. In addition, Sn(OH) 3.0 Cl 1.0 The powder loss rate of the PVC-PVB ball after 1000 cycles is only 0.53%, proving that the soft and hard skeleton of the PVC-PVB dual binder can make the Sn(OH) 3.0 Cl 1.0 / PVC-PVB adsorbent beads form an extensive adsorption channel, while also avoiding Sn(OH) 3.0 Cl 1.0 / The loss of effective powder in the PVC-PVB beads greatly improves the adsorption capacity and adsorption stability of the fluorine adsorbent.
[0197] Application Example 3
[0198] The fluorine adsorbent Sn(OH) prepared in Example 3 was 3.0 Cl 1.0 / PVC-PVB balls were used for application tests.
[0199] See also Figure 2 The fluorine-containing wastewater treatment application process based on the fluorine adsorbent of Example 3 includes:
[0200] (1) Wastewater defluorination process: The fluorine adsorbent beads prepared in Example 3 are loaded into the adsorption column. The fluorine ion concentration of the fluorine-containing wastewater is about 200 mg / L. The fluorine-containing wastewater flows into the adsorption column from bottom to top at a flow rate of 20 BV. The fluorine ion concentration in the produced water after defluorination is less than 1 mg / L. A fluorine ion sensor is installed at the water outlet to monitor the fluorine ion concentration of the produced water in real time online. Once the fluorine ion concentration of the produced water is greater than 1 mg / L, the adsorption of the water is stopped and regeneration is prepared.
[0201] (2) Fluorine adsorbent regeneration process: When the fluorine ion concentration of the adsorption column of the fluorine adsorbent is greater than 1mg / L, the 3mol / L MgCl2 solution in the regeneration liquid storage tank A is used as the regeneration liquid to regenerate the fluorine adsorbent from bottom to top at a flow rate of 25BV / h. The regeneration liquid storage tank A and the adsorption column are used as a circulation system. The upper water of the adsorption column is returned to the regeneration liquid storage tank A. The regeneration liquid volume is 4BV. The circulation is 20 minutes to complete the regeneration of the fluorine adsorbent. After the regeneration is completed, all the residual regeneration liquid in the adsorption column is pumped back to the regeneration liquid storage tank A.
[0202] (3) Regeneration liquid reuse process: After the regeneration liquid (3 mol / L MgCl2 solution) regenerates the fluorine adsorbent, an eluent (a mixture of MgCl2 solution and MgF2 precipitate, wherein the MgCl2 concentration is less than 3 mol / L) is obtained, and the eluent is pumped into a plate-frame filter press to perform solid-liquid separation of the MgCl2 solution and the MgF2 precipitate, and the obtained MgCl2 solution (filtrate) is pumped back to the regeneration liquid storage tank B. After the eluent in the regeneration liquid storage tank A has all flowed through the plate-frame filter press, the slightly lower concentration MgCl2 solution (filtrate) in the regeneration liquid storage tank B is pumped into the regeneration liquid storage tank A, and an appropriate amount of MgCl2·6H2O solid is added to the regeneration liquid storage tank A to obtain a 3 mol / L MgCl2 solution that is used as a new regeneration liquid for recycling. The MgF2 filter cake is dried and crushed to obtain MgF2 powder, which can be sold as a chemical.
[0203] Figure 8 Example 3 fluorine adsorbent Sn(OH) provided for this application example 3.0 Cl 1.0 / The regular curve diagram of fluorine concentration in influent and outfluent water during the defluorination operation of PVC-PVB balls in real fluorine-containing industrial wastewater.
[0204] from Figure 8It can be seen that the fluoride ion concentration in the water produced by the fluoride adsorbent during the fluoride removal process is very stable. The fluoride ion concentration in the fluoride-containing groundwater inlet is about 200 mg / L, and the fluoride ion concentration in the water produced is always less than 0.5 mg / L before the column adsorption is saturated. China's "National Drinking Water Quality Standard" (GB5749-2022) stipulates that the limit value of fluoride in drinking water is 1.0 mg / L, which proves that the fluoride adsorbent can meet the national standard requirements for groundwater defluoridation and also meet engineering needs. It has the advantages of large adsorption capacity and stable adsorption performance, and is expected to be able to be applied on a large scale.
[0205] In addition, the purity of the MgF2 powder product obtained by using the above-mentioned fluorine adsorbent to remove fluorine from fluorine-containing groundwater is 99.75%, which can be sold as a high-value-added product. This proves that the fluorine adsorbent can realize the resource utilization of sewage and turn waste into treasure.
[0206] Comparative Example 1
[0207] A method for preparing a fluorine adsorbent, the method comprising:
[0208] (I) Solution preparation: Same as Example 1.
[0209] (ii) Precipitation reaction: Same as Example 1.
[0210] (III) Oxidation reaction: Same as Example 1.
[0211] (IV) Drying and pulverizing: Same as Example 1.
[0212] (V) Powder granulation:
[0213] Sn(OH) with a particle size of 0.5-5 μm 4-x F x Light yellow dry powder, polyvinyl chloride (PVC), and N,N-dimethylacetamide (DMAC) are mixed in a certain mass ratio, wherein the mass of the binder PVC accounts for 1.3% of the total powder mass (Sn(OH) 4-x F x +PVC), the mass of solvent DMAC accounts for 8% of the total powder mass (Sn(OH) 4-x F x +PVC).
[0214] Add the materials to the stirred tank in this order: first add the solvent DMAC, heat to 50°C, add the binder PVC while stirring, and after the binder PVC is dissolved, add Sn(OH) 4-x F x Light yellow dry powder, continue stirring for 1h. Transfer the liquid to the ball dropping device for ball dropping, and the small ball falls into deionized water for phase conversion to obtain Sn(OH) with a particle size of 0.5mm 4-x F x / PVC small balls.
[0215] (VI) Fluorine-chlorine replacement: 100L of Sn(OH) 4-x F x / PVC balls were loaded into the adsorption column, and the above-prepared NaCl-NaHCO3 solution with a pH of 7.5 was added from the bottom of the adsorption column at a flow rate of 1BV / h. The amount of NaCl-NaHCO3 solution was 150L, and the Sn(OH) 4-x F x / PVC small balls, making Sn(OH) 4-x F x / The fluorine element on the PVC ball is replaced by the chlorine element in the NaCl--NaHCO3 solution, Sn(OH) 4-x F x / PVC pellets transformed into Sn(OH) 4-x Cl x / PVC small balls.
[0216] Table 4 Analysis of adsorption capacity and powder loss rate of fluorine adsorbents in Example 1 and Comparative Example 1:
[0217] Saturated adsorption capacity of Example 1 (mg / g) 115 Powder loss rate of Example 1 after 1000 cycles of use 0.5% Saturated adsorption capacity of comparative example 1 (mg / g) 107 Powder loss rate of comparative example 1 after 1000 cycles of use 35.6%
[0218] Through testing, this comparative example Sn(OH) 4-x Cl x The powder loss rate of the PVC ball after 1000 cycles is as high as 35.6%, which is 71 times that of Example 1, proving that using only PVC as a single binder cannot avoid the Sn(OH) 4- x Cl x / The loss of effective powder in the PVC balls greatly reduces the adsorption stability of the fluorine adsorbent.
[0219] The difference between the fluorine adsorbent synthesis method of this comparative example and that of Example 1 is that a single PVC binder is used for powder granulation.
[0220] Comparative Example 2
[0221] A method for preparing a fluorine adsorbent, the method comprising:
[0222] (I) Solution preparation: Same as Example 1.
[0223] (ii) Precipitation reaction: Same as Example 1.
[0224] (III) Oxidation reaction: Same as Example 1.
[0225] (IV) Drying and pulverizing: Same as Example 1.
[0226] (V) Powder granulation:
[0227] Sn(OH) with a particle size of 0.5-5 μm 4-x F x Light yellow dry powder, polyvinyl butyral (PVB), and N,N-dimethylacetamide (DMAC) are mixed in a certain mass ratio, wherein the total mass of the binder PVB accounts for 1.3% of the total powder mass (Sn(OH) 4-x F x +PVB), the mass of solvent DMAC accounts for 8% of the total powder mass (Sn(OH) 4-x F x +PVB).
[0228] Add the materials to the stirred tank in this order: first add the solvent DMAC, heat to 50°C, add the binder PVB while stirring, and after the binder PVB is dissolved, add Sn(OH) 4-x F x Light yellow dry powder, continue stirring for 1h. Transfer the liquid to the ball dropping device for ball dropping, and the small ball falls into deionized water for phase conversion to obtain Sn(OH) with a particle size of 0.5mm 4- x F x / PVB balls.
[0229] (VI) Fluorine-chlorine replacement: 100L of Sn(OH) 4-x F x / PVB beads were loaded into the adsorption column, and the above-prepared NaCl-NaHCO3 solution with a pH of 7.5 was added from the bottom of the adsorption column at a flow rate of 1BV / h. The amount of NaCl-NaHCO3 solution used was 150L to fully soak the Sn(OH) 4-x F x / PVB beads, making Sn(OH) 4-x F x / The fluorine element on the PVB ball is replaced by the chlorine element in the NaCl--NaHCO3 solution, Sn(OH) 4-x F x / PVB beads transformed into Sn(OH) 4-x Cl x / PVB balls.
[0230] Table 5 Analysis of adsorption capacity and powder loss rate of fluorine adsorbents in Example 1 and Comparative Example 2:
[0231] Saturated adsorption capacity of Example 1 (mg / g) 115 Powder loss rate of Example 1 after 1000 cycles of use 0.5% Saturated adsorption capacity of comparative example 2 (mg / g) 102 Powder loss rate of comparative example 2 after 1000 cycles of use 45.7%
[0232] Through testing, this comparative example Sn(OH) 4-x Cl xThe powder loss rate of the PVB beads after 1000 cycles is as high as 45.7%, which is 91 times that of Example 1, proving that using only PVB as a single binder cannot avoid the Sn(OH) 4- x Cl x / The loss of effective powder in the PVB beads greatly reduces the adsorption stability of the fluorine adsorbent.
[0233] The difference between the fluorine adsorbent synthesis method of this comparative example and that of Example 1 is that a single PVB binder is used for powder granulation.
[0234] Comparative Example 3
[0235] This comparative example is the same as Example 1 except that the "NaCl-NaHCO3 solution with a pH of 7.5-8.5" in step (six) is replaced by "pure NaCl solution".
[0236] The comparative example was compared with the adsorption test of Example 1. It can be seen that in the "fluorine-chlorine replacement" stage, the use of pure NaCl solution instead of the NaCl-NaHCO3 solution with a pH of 7.5 to 8.5 resulted in Sn(OH) 4-x F x Cannot be converted into Sn(OH) 4-x Cl x , resulting in an adsorption capacity of only 37 mg / g, which is only 32% of that in Example 1.
[0237] Table 6 Analysis of adsorption capacity of fluorine adsorbents in Example 1 and Comparative Example 3:
[0238]
[0239]
[0240] Comparative Example 4
[0241] A method for preparing a fluorine adsorbent, the method comprising:
[0242] (I) Solution preparation:
[0243] Preparation of SnCl2-citric acid solution: same as Example 1.
[0244] Preparation of NaF-Na2CO3 solution: Na2CO3 powder is added to deionized water to prepare a saturated Na2CO3 solution, and then NaF powder is added to the saturated Na2CO3 solution so that the concentration of NaF in the prepared NaF-Na2CO3 solution is 0.02 mol / L to obtain a NaF-Na2CO3 solution.
[0245] Preparation of NaCl-NaHCO3 solution: same as in Example 1.
[0246] (ii) Precipitation reaction: Same as Example 1.
[0247] (III) Oxidation reaction: Same as Example 1.
[0248] (IV) Drying and pulverizing: Same as Example 1.
[0249] (V) Powder granulation: Same as Example 1.
[0250] (VI) Fluorine-chlorine replacement: Same as Example 1.
[0251] Comparison of the adsorption test between Comparative Example 4 and Example 1 shows that in the "solution preparation" stage, the concentration of NaF in the prepared NaF-Na2CO3 solution is 0.02 mol / L, resulting in Sn(OH) 4-x Cl x The x in Example 1 is 0.2, resulting in an adsorption capacity of only 19 mg / g, which is only 16.5% of that in Example 1.
[0252] Table 7 Analysis of adsorption capacity of fluorine adsorbents in Example 1 and Comparative Example 4:
[0253] The chemical formula of the fluorine adsorbent of Example 1 is <![CDATA[Sn(OH) 3.2 Cl 0.8 ]]> Saturated adsorption capacity of Example 1 (mg / g) 115 The chemical formula of the fluorine adsorbent of Comparative Example 4 is <![CDATA[Sn(OH) 3.8 Cl 0.2 ]]> Saturated adsorption capacity of comparative example 4 (mg / g) 19
[0254] The difference between the fluorine adsorbent synthesis method of this comparative example and that of Example 1 is that Sn(OH) 4-x Cl x where x is 0.2.
[0255] Application Comparative Example 1
[0256] The fluorine adsorbent Sn(OH) prepared in Example 1 was 3.2 Cl 0.8 / PVC-PVB balls were used for application tests.
[0257] See also Figure 2 The fluorine-containing wastewater treatment application process based on the fluorine adsorbent of Example 1 includes:
[0258] (1) Wastewater defluorination process: same as application example 1.
[0259] (2) Fluorine adsorbent regeneration process: When the fluorine ion concentration of the adsorption column of the fluorine adsorbent is greater than 1mg / L, the 0.1mol / L MgCl2 solution in the regeneration liquid storage tank A is used as the regeneration liquid to regenerate the fluorine adsorbent from bottom to top at a flow rate of 15BV / h. The regeneration liquid storage tank A and the adsorption column are used as a circulation system. The upper water of the adsorption column is returned to the regeneration liquid storage tank A. The regeneration liquid volume is 2BV. The circulation is 10 minutes to complete the regeneration of the fluorine adsorbent. After the regeneration is completed, all the residual regeneration liquid in the adsorption column is pumped back to the regeneration liquid storage tank A.
[0260] (3) Regeneration liquid reuse process: same as application example 1.
[0261] The difference between this comparative application example and the application example is that this comparative application example uses a MgCl2 solution with a concentration of 0.1 mol / L as the regeneration solution. As can be seen from Table 8, when the concentration of the MgCl2 solution used is too low, the fluorine adsorbent will be incompletely regenerated. Incomplete regeneration will make it difficult to obtain the same performance as the initial adsorption capacity in the next adsorption process, resulting in a low cyclic adsorption capacity, which is only 51% of Example 1.
[0262] Table 8 Analysis of cyclic adsorption capacity of fluorine adsorbent in Example 1 and Comparative Example 1:
[0263]
[0264] Application Comparative Example 2
[0265] The fluorine adsorbent Sn(OH) prepared in Example 1 was 3.2 Cl 0.8 / PVC-PVB balls were used for application tests.
[0266] See also Figure 2 The fluorine-containing wastewater treatment application process based on the fluorine adsorbent of Example 1 includes:
[0267] (1) Wastewater defluorination process: same as application example 1.
[0268] (2) Fluorine adsorbent regeneration process: When the fluorine ion concentration of the adsorption column of the fluorine adsorbent is greater than 1mg / L, the 4mol / L MgCl2 solution in the regeneration liquid storage tank A is used as the regeneration liquid to regenerate the fluorine adsorbent from bottom to top at a flow rate of 15BV / h. The regeneration liquid storage tank A and the adsorption column are used as a circulation system. The upper water of the adsorption column is returned to the regeneration liquid storage tank A. The regeneration liquid volume is 2BV. The circulation is 10 minutes to complete the regeneration of the fluorine adsorbent. After the regeneration is completed, all the residual regeneration liquid in the adsorption column is pumped back to the regeneration liquid storage tank A.
[0269] (3) Regeneration liquid reuse process: same as application example 1.
[0270] The difference between this comparative example and the application example is that this comparative example uses a 4 mol / L MgCl2 solution as the regeneration solution. As shown in Table 9, when the concentration of the MgCl2 solution used is too high, the precipitation reaction driving force Mg 2+ +2F - = The presence of MgF2↓, the excessive concentration of Mg in the regeneration solution 2+, the formed MgF2 precipitate particles will be too large, blocking the adsorption and desorption channels of the fluorine adsorbent, and the MgF2 precipitate particles cannot flow out of the adsorption column with the regeneration liquid flow, making it difficult to carry out the next cycle of adsorption and desorption, resulting in a low cyclic adsorption capacity of only 12.5% of that in Example 1.
[0271] Table 9 Analysis of cyclic adsorption capacity of fluorine adsorbents in Example 1 and Comparative Example 2:
[0272]
[0273] Application Comparative Example 3
[0274] The fluorine adsorbent Sn(OH) prepared in Example 1 was 3.2 Cl 0.8 / PVC-PVB balls were used for application tests.
[0275] See also Figure 2 The fluorine-containing wastewater treatment application process based on the fluorine adsorbent of Example 1 includes:
[0276] (1) Wastewater defluorination process: same as application example 1.
[0277] (2) Fluorine adsorbent regeneration process: When the fluorine ion concentration of the adsorption column of the fluorine adsorbent is greater than 1mg / L, the 0.5mol / L MgCl2 solution in the regeneration liquid storage tank A is used as the regeneration liquid to regenerate the fluorine adsorbent from bottom to top at a flow rate of 10BV / h. The regeneration liquid storage tank A and the adsorption column are used as a circulation system. The upper water of the adsorption column is returned to the regeneration liquid storage tank A. The regeneration liquid volume is 2BV. The circulation is 10min to complete the regeneration of the fluorine adsorbent. After the regeneration is completed, all the residual regeneration liquid in the adsorption column is pumped back to the regeneration liquid storage tank A.
[0278] (3) Regeneration liquid reuse process: same as application example 1.
[0279] The difference between this comparative application example and the application example is that this comparative application example regenerates the fluorine adsorbent from bottom to top at a flow rate of 10 BV / h. As can be seen from Table 10, when the flow rate of the regeneration liquid used is too small, the liquid flow rate between the particles will be too small, and the formed MgF2 precipitate particles will not be able to flow out of the adsorption column with the water flow, which will block the adsorption and desorption channels of the fluorine adsorbent, making it difficult to carry out the adsorption and desorption of the next cycle, thereby resulting in a low cycle adsorption capacity, which is only 28.5% of Example 1.
[0280] Table 10 Analysis of the cyclic adsorption capacity of the fluorine adsorbent in Example 1 and Comparative Example 3:
[0281]
[0282] Application Comparative Example 4
[0283] The fluorine adsorbent Sn(OH) prepared in Example 1 was 3.2 Cl 0.8 / PVC-PVB balls were used for application tests.
[0284] See also Figure 2 The fluorine-containing wastewater treatment application process based on the fluorine adsorbent of Example 1 includes:
[0285] (1) Wastewater defluorination process: same as application example 1.
[0286] (2) Fluorine adsorbent regeneration process: When the fluorine ion concentration of the adsorption column of the fluorine adsorbent is greater than 1mg / L, the 0.5mol / L MgCl2 solution in the regeneration liquid storage tank A is used as the regeneration liquid to regenerate the fluorine adsorbent from bottom to top at a flow rate of 30BV / h. The regeneration liquid storage tank A and the adsorption column are used as a circulation system. The upper water of the adsorption column is returned to the regeneration liquid storage tank A. The regeneration liquid volume is 2BV. The circulation is 10 minutes to complete the regeneration of the fluorine adsorbent. After the regeneration is completed, all the residual regeneration liquid in the adsorption column is pumped back to the regeneration liquid storage tank A.
[0287] (3) Regeneration liquid reuse process: same as application example 1.
[0288] The difference between this comparative application example and the application example is that this comparative application example regenerates the fluorine adsorbent from bottom to top at a flow rate of 30 BV / h. As can be seen from Table 11, when the flow rate of the regeneration liquid used is too large, due to the flushing of the water flow, serious collisions and mutual frictions between the fluorine adsorbent particles will occur, resulting in serious powder loss of the fluorine adsorbent, and the effective powder of the fluorine adsorbent will flow to the outside of the adsorption column with the water flow, resulting in a sharp decrease in the effective content of the fluorine adsorbent in the column, thereby resulting in a low cyclic adsorption capacity, which is only 24% of Example 1.
[0289] Table 11 Analysis of cyclic adsorption capacity of fluorine adsorbents in Example 1 and Comparative Example 4:
[0290]
[0291] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A fluorine adsorbent, characterized in that: The structural formula of the fluorine adsorbent is: Sn(OH) 4-x Cl x / PVC-PVB, where: 0.8≤x≤1.0; The PVC-PVB is a dual binder, and the fluorine adsorbent is prepared by using PVC and PVB as binders.
2. The fluorine adsorbent according to claim 1, characterized in that The fluorine adsorbent is a spherical structure, and the particle size of the fluorine adsorbent is 0.5-2 mm.
3. A method for preparing the fluorine adsorbent according to claim 1, characterized in that: The preparation method comprises: Step S1: Precipitation reaction: NaF-Na2CO3 solution is added dropwise to SnCl2-citric acid solution to perform precipitation reaction to obtain Sn(OH) 2-x F x Slurry; Step S2 Oxidation reaction: Sn(OH) 2-x F x The slurry is oxidized to make Sn(OH) 2-x F x Transformed to Sn(OH) 4-x F x , Sn(OH) 4-x F x Slurry; Step S3 Drying and Powdering: Sn(OH) 4-x F x The slurry was filtered to obtain Sn(OH) 4-x F x The filter cake is then dried and crushed to obtain Sn(OH) with a particle size of 0.5 to 20 μm. 4-x F x Powder; Step S4: Powder granulation: Sn(OH) 4-x F x Powder, PVC and PVB are added to the solvent to obtain a granulation solution; then drop ball granulation is performed to obtain Sn(OH) with a particle size of 0.5 to 2 mm. 4-x F x / PVC-PVB small balls; Step S5: Fluorine-chlorine replacement: Sn(OH) 4-x F x / PVC-PVB beads are subjected to fluorine-chlorine replacement to obtain spherical fluorine adsorbent.
4. The method for preparing the fluorine adsorbent according to claim 3, characterized in that: The dropping speed of the NaF-Na2CO3 solution in step S1 is 10 to 50 L / h; And / or, the oxidation in step S2 is carried out by aeration; Preferably, the oxidation is carried out by aerating Sn(OH) at a rate of 10 to 30 L / min. 2-x F x Air is introduced into the slurry.
5. The method for preparing the fluorine adsorbent according to claim 3, characterized in that: The drying temperature in step S3 is 50-80°C, and after drying, Sn(OH) 4-x F x The moisture content of the powder is less than 5%; And / or, the solvent in step S4 is N,N-dimethylacetamide; And / or, the mass of the solvent in step S4 is 75-150% of the total mass of the granulation raw material; the total mass of the granulation raw material is Sn(OH) 4-x F x The sum of the mass of powder, PVC and PVB; And / or, the pH value of the NaCl-NaHCO3 solution in step S5 is 7.5-8.
5.
6. The method for preparing the fluorine adsorbent according to claim 5, characterized in that: In step S4, the mass of PVC and PVB accounts for 8-25% of the total mass of the granulation raw materials; And / or, in step S4, the mass ratio of PVC to PVB is 1:1-5.
7. Use of the fluorine adsorbent according to claim 1 or 2 in the treatment of fluorine-containing wastewater.
8. A method for treating fluorine-containing wastewater using a fluorine adsorbent according to claim 1 or 2, characterized in that: The processing method comprises: (A) Defluorination of wastewater; (B) fluorine adsorbent regeneration; (C) The regeneration liquid is reused.
9. The method for treating fluorine-containing wastewater according to claim 8, characterized in that: The wastewater defluorination comprises: filling the fluorine adsorbent according to claim 1 or 2 into an adsorption column, then flowing the fluorine-containing wastewater into the adsorption column for defluorination, and when the fluorine ion concentration is greater than 1 mg / L, stopping the flow of the fluorine-containing wastewater and regenerating the fluorine adsorbent; And / or, the fluorine adsorbent regeneration includes: using MgCl2 solution as regeneration liquid to circulate and elute the fluorine adsorbent adsorbed with fluorine ions, completing the regeneration of the fluorine adsorbent, and obtaining an eluent containing MgCl2 solution and MgF2 precipitate; Preferably, the concentration of the MgCl2 solution is 0.5-3 mol / L.
10. The method for treating fluorine-containing wastewater according to claim 9, characterized in that: The regeneration liquid reuse comprises: (C1) performing solid-liquid separation on the eluate containing the MgCl2 solution and the MgF2 precipitate to obtain a MgCl2 solution and a MgF2 precipitate; (C2) adjusting the concentration of the MgCl2 solution to 0.5-3 mol / L for recycling as a regeneration solution; And, the MgF2 precipitate is dried to obtain MgF2 powder.
Citation Information
Patent Citations
Method and device for sequencing batch treatment of fluorine / nickel-containing acidic wastewater in aluminum profile production
CN104326602A
Fluorine adsorbent
JP1986287443A
Fluorine-containing wastewater treatment method using fluorine adsorbent
JP2005144369A
Method for treating fluorine ion-containing wastewater by fluorine adsorbent
JP2011194335A
Remover of fluoride ion and treatment method for wastewater comprising fluoride ion using the same
KR1020010070640A